2017
DOI: 10.3892/mmr.2017.7569
|View full text |Cite
|
Sign up to set email alerts
|

DhHP-6 attenuates cerebral ischemia-reperfusion injury in rats through the inhibition of apoptosis

Abstract: As a novel reactive oxygen species (ROS) scavenger, deuterohemin His peptide-6 (DhHP-6) has been demonstrated to prolong the lifespan of Caenorhabditis elegans and has also exhibited protective effects in myocardial ischemia-reperfusion injury. Whether similar effects occur during cerebral ischemia-reperfusion (CIR) injury remains to be elucidated. The present study evaluated the function of DhHP-6 and its underlying mechanisms in a middle cerebral artery occlusion (MCAO) model in rats. The focal transient MCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Neuro‐apoptosis is the key process associated with the pathogenesis of brain injury [30‐32]. The autophagy inducer rapamycin prevented ischemia reperfusion‐induced brain injury by regulating apoptosis by upregulating autophagy in the rat penumbra [33].…”
Section: Discussionmentioning
confidence: 99%
“…Neuro‐apoptosis is the key process associated with the pathogenesis of brain injury [30‐32]. The autophagy inducer rapamycin prevented ischemia reperfusion‐induced brain injury by regulating apoptosis by upregulating autophagy in the rat penumbra [33].…”
Section: Discussionmentioning
confidence: 99%
“…283,284 It is reported that inhibition of NF-κB pathway activation is involved in breaking cellular redox homeostasis and triggers ROS production and accumulation through the JNK-mitogen-activated protein kinase (MAPK) axis. 285,286 Due to high specificity and the power to cross the BBB, exosome-and nanovesicle-mediated delivery [287][288][289] of peptides, [290][291][292][293] small molecules, miRNA, [294][295][296] and other drugs in Fig. 3 Steps of focal cerebral ischemia development…”
Section: Therapeutic Approaches For Ischemia and Gliomamentioning
confidence: 99%
“…Neuronal apoptosis occurs during cerebral ischemia and reperfusion injury, as well as glial cells and vascular endothelial cells. Recent studies have shown that the pathways that regulate apoptosis mainly include the mitochondrial, the death receptor, and the endoplasmic reticulum pathways [35,36]. In this study, in the rat model of CIRI induced by MCAO, EA had a protective role through the miR-223/PTEN pathway.…”
Section: Discussionmentioning
confidence: 58%
“…CIRI results in necrosis or apoptosis of nerve cells, which plays a crucial role in neurological deficits caused by cerebral infarction [35]. Neuronal apoptosis occurs during cerebral ischemia and reperfusion injury, as well as glial cells and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%